Do reduced numbers of plasmacytoid dendritic cells contribute to the aggressive clinical course of COVID‐19 in chronic lymphocytic leukaemia?. (16th March 2022) - Smith, Carl Inge Edvard; Zain, Rula; Österborg, Anders; Palma, Marzia; Buggert, Marcus; Bergman, Peter; Bryceson, Yenan
Abstract: Infections with SARS‐CoV‐2 have been unduly severe in patients with haematological malignancies, in particular in those with chronic lymphocytic leukaemia (CLL). Based on a series of observations, we propose that an underlying mechanism for the aggressive clinical course of COVID‐19 in CLL is a paucity of plasmacytoid dendritic cells (pDCs) in these patients. Indeed, pDCs express Toll‐like receptor 7 (TLR7), which together with interferon‐regulatory factor 7 (IRF7), enables pDCs to produce large amounts of type I interferons, essential for combating COVID‐19. Treatment of CLL with Bruton's tyrosine kinase (BTK) inhibitors increased the number of pDCs, likely secondarily to the reduction in the tumour burden.